Modulation of the Fc gamma RII and Fc gamma RIII induced by GM-CSF, IFN-gamma and IL-4 on murine eosinophils. - de Andrés, B (1994)
Murine eosinophils express the low-affinity Fc gamma receptors recognized by the monoclonal antibody (mAb) 2.4G2, which are involved in the activation of these cells. We have studied the membrane and RNA expression of the low-affinity Fc gamma receptors on murine eosinophils stimulated by granulocyte-macrophage colony-stimulating factor (GM-CSF), interferon-gamma (IFN-gamma), and interleukin-4 (IL-4). Flow cytometric analysis (FACS) of eosinophils incubated with GM-CSF and IFN-gamma showed an up-regulation on the expression of these receptors with a maximal effect at 24 hr. IL-4 failed to induce any positive or negative effect in these cells. To assess the pattern of expression of the low-affinity Fc gamma receptors on eosinophils, Northern blot analyses were carried out using specific cDNA probes encoding for the Fc gamma RII and Fc gamma RIII. Murine eosinophils constitutively express transcripts for Fc gamma RII and RIII. Incubation with GM-CSF from 3 to 12 hr produced a potent induction of the two transcripts studied (Fc gamma RII and RIII). IFN-gamma did not induce any important up-regulation of the two transcripts from 3 to 12 hr of incubation. By contrast, IL-4 produced a marked inhibition of both transcripts at 24 hr of incubation. Expression of the gamma-chain transcript which is associated with Fc gamma RIII has been detected on freshly isolated eosinophils. This study demonstrates a different regulation pattern of these receptors depending on the cytokine or growth factor used to stimulate murine eosinophils.